REPRESENTATION OF ICONIC CULTURE IN SOUTHEAST ASIAN IN “RAYA AND THE LAST DRAGON” - Anak Agung Sagung Sonia Sarwindah; Lambok Hermanto Sihombing (Haluan Sastra Budaya, 2022)
This study discusses the representation of iconic culture in Southeast Asia in the movie. This research focuses on findings of the scene that shows the iconic culture of Southeast Asian in the film Raya and The Last Dragon. The qualitative method is applied to analyze the data in this study and the applied theory is representation theory by Stuart Hall and culture theory. Therefore, the result of this research shows the representation of iconic culture from Indonesia, Thailand, and Philippines, the iconic culture itself is detailed represented and recognizable. The first iconic culture is the weapon used by Indonesian in the form of traditional weaponry. The form of iconic culture from Thailand is represented through the vehicle used by Raya. This vehicle is the iconic mode of transportation that can be found in Thailand. Finally, the Martial Arts used in the scenes are the Philippines iconic culture.